'Ilima', 'Izithebe' and the 'Green Revolution' : a complex agro-ecological approach to understanding agriculture in Pondoland and what this means for sustainability through the creation of 'Living Landscapes' - Payn, Valerie (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.